(untitled) (Journal of Partial Differential Equations, 2024)
The purpose of this paper is to study scattering theory for the energy subcritical solutions to the non-radial defocusing inhomogeneous Hartree equation i_tu+Δ u=(I_α*|·|^b|u|^p)|·|^b|u|^p-2u. Taking advantage of the decay factor in the nonlinearity instead of the embedding theorem, we establish the scattering criterion for the equation. Together with the Morawetz estimate, we obtain the scattering theory for the energy-subcritical case.